The impact of momentum trades on return comovements and asymmetric volatility in dual listings - Dey, Malay K.; Wang, Chaoyan (Unpublished, 2018)
We empirically investigate the impact of volume on serial return comovements (continuation vs. reversal) and asymmetric volatility (inverse relation with excess return) of 175 ADRs and their underlying securities in 27 countries. We classify +/-/0 trade momentum days based on a joint distribution of volume and return and determine how momentum affects return comovements and asymmetric volatility. Our VAR estimates confirm asymmetric volume comovements, positive volume return correlations implying continuation, and non-monotonic effects of excess return on volatility among ADRs and their underlying home shares. Return comovements and asymmetric volatility are associated with momentum, size, and liquidity.